Examining The Impact Of Computer-Based Assessment On Higher Education Student Performance In Kano, Nigeria - Bello, Hassan (2024)
Although scholars have explored the drivers of students’ Computer-Based Assessment (CBA) intention, actual responses to CBA, and the impact of CBA on student performance, the intention-performance link remain under-explored. Thus, this study aimed to investigate the impact of CBA on student performance in Kano, Nigeria and suggests that factors such as students' goal expectancy and technology readiness influence their performance with the CBA system. Additionally, this study explores how service satisfaction affects overall satisfaction and thus influences student performance within the CBA system. The study merged the Expectation Confirmation Model (ECM), the Information System Success Model (ISSM), and the Technology Readiness Model (TRI 2.0) to examine the research framework. Survey data collected from 459 undergraduate students in selected higher education institutions in Kano who used the CBA system to test the framework. The study reveals that the impact of the CBA system on individual performance of Kano state higher education students depends not only on the continuance intention of the system but also on students’ satisfaction. The findings further indicate that goal expectancy and technology readiness negatively influence the connection between continuance intention and individual performance. These findings suggest that continuance use intention, overall satisfaction, goal expectancy, and technology readiness facilitate the individual performance of the CBA system. In addition, the results demonstrated that service satisfaction mediates between system quality, service quality, and overall satisfaction. Moreover, the study established that service satisfaction is the most significant factor xix that affects the overall success of the in-campus CBA system.